2013
DOI: 10.11158/saa.18.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Mites (Acari) associated with three species of the genus <em>Jatropha</em> (Euphorbiaceae) in Brazil, with emphasis on <em>Jatropha curcas</em>

Abstract: dalfran@cnpa.embrapa.br RESUMO -O pinhão manso desponta como uma das principais fontes renováveis para obtenção de biocombustível. Pouco é conhecido sobre as pragas e doenças que atacam esta euforbiácea. Os Tarsonemidae são ácaros de hábitos bastante diversos tendo como principal representante o ácaro branco Polyphagotarsonemus latus. Esta praga ataca aproximadamente 60 famílias de plantas, dentre as quais espécies de importância agrícola e ornamentais. Com o objetivo de descrever taxonomicamente a espécie de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These four species have been frequently found in Brazil, both on cultivated plants (e.g. Mineiro et al 2004, Hernandes & Feres 2006, Rezende & Lofego 2012, Silva et al 2012, Lofego et al 2013, Domingos et al 2014, Baldo et al 2018) and on plants of the Amazon Forest (Nuvoloni et al 2015b), Cerrado (Lofego et al 2004, Demite et al 2009, Rezende & Lofego 2011), and Pantanal (Mendonça et al 2019. In Mato Grosso State, E. alatus was previously reported from rubber trees (Ferla & Moraes 2002), while E. citrifolius, E. concordis and I. zuluagai were reported from rubber trees (Feres 2000, Feres et al 2002, Demite & Feres 2007, Daud & Feres 2013 and from plants of the Cerrado vegetation (Demite et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These four species have been frequently found in Brazil, both on cultivated plants (e.g. Mineiro et al 2004, Hernandes & Feres 2006, Rezende & Lofego 2012, Silva et al 2012, Lofego et al 2013, Domingos et al 2014, Baldo et al 2018) and on plants of the Amazon Forest (Nuvoloni et al 2015b), Cerrado (Lofego et al 2004, Demite et al 2009, Rezende & Lofego 2011), and Pantanal (Mendonça et al 2019. In Mato Grosso State, E. alatus was previously reported from rubber trees (Ferla & Moraes 2002), while E. citrifolius, E. concordis and I. zuluagai were reported from rubber trees (Feres 2000, Feres et al 2002, Demite & Feres 2007, Daud & Feres 2013 and from plants of the Cerrado vegetation (Demite et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-one phytoseiid species have been reported from Bahia ( Bonato et al 1999 ; Denmark and Muma 1973 ; Farias et al 1981 ; Fiaboe et al 2004 , 2007 ; Lawson-Balagbo et al 2008 ; Lofego et al 2000 , 2013 ; Moraes et al 1993 , 1994 , 1997 ; Moraes and Denmark 1999 ; Moraes and McMurtry 1983 ; Noronha et al 1997 ; Noronha and Moraes 1989 ; Oliveira et al 2007 ; Souza et al 2010 , 2012 ). In the present study, fifteen species are reported for the first time in that state, raising the number of known species to sixty-six.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were mounted on slides using Hoyer's medium and evaluated using a stereo microscope. Specimen identification was performed using the dichotomous keys by CHANT;MCMURTRY (1994), LOFEGO (1998), andMORAES et al (2004) for mites from the family Phytoseiidae; PRITCHARD;BAKER (1995) and BOLLAND et al (1998) for mites from the family Tetranychidae; WELBOURN et al (2003) for mites from the family Tenuipalpidae; GERSON et al (1999) for mites from the family Cheyletidae; and HALLIDAY et al (1998) for mites from the families Ascidae and Blattisocidae. Slides were deposited in the collection of the laboratory of Functional and Applied Ecology of UFT.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the potential use of Jatropha curcas L. for biofuel production (ALONSO; LEZCANO, 2014), integrated management studies of pest arthropods associated with this crop are necessary for optimizing its production. For example, phytophagous mites are usually reported to be potential pests of J. curcas (SARMENTO et al, 2011;CRUZ et al, 2013a;LOFEGO et al, 2013;PEDRO-NETO et al, 2013;ROSADO et al, 2015a;2015b;SARAIVA et al, 2015). Predatory mites, especially those in the family Phytoseiidae, also colonize J. curcas plants and play a key role in limiting phytophage population (SARMENTO et al, 2011).…”
Section: Introductionmentioning
confidence: 99%